Avaliação do método Drastic na estimativa da vulnerabilidade intrínseca das águas subterrâneas no Sistema Jacaré-Tietê/Sp - Tanajura, Douglas Da Silva [UNIFESP] (2018)
Water is the most precious natural resource on Earth planet. Understanding the hydric dynamics of groundwater has resulted in socioeconomic advances and new perspectives for the native populations of previously inhospitable regions. In the opposite direction of the improvement process of the life quality, it’s increasing the presence of anthropic activities with exacerbated consumption of water and with high polluting potential. The various difficulties found in increasingly complex contamination scenarios shown that preventive control of soil and land use is indispensable for the management of water resources in more vulnerable areas. In an attempt to meet this challenge, due to its importance in the scientific literature and its application in studies worldwide, the DRASTIC was defined as the method for assessing the groundwater intrinsic vulnerability in the area of the Jacaré-Tietê System. The vulnerability mapping allowed the observation of systematic problems in the structure of the DRASTIC method, mainly the low sensitivity of the parameters Recharge and Hydraulic Conductivity in the scale of this work, keeping constant all over the study area. In view of this, were proposed modifications in the approach of the parameters Recharge and Hydraulic Conductivity, and new classes of vulnerability aiming the prioritization of more susceptible areas to contamination. In the framework of the proposed modifications, the Recharge parameter has modified to be delimited by the spatial limits of the geologic formations, and the Hydraulic Conductivity parameter was replaced by the Soil Coverage parameter, in order to significantly improve its spatial sensitivity in obtaining and mapping the vulnerability. The obtained results shown the made modifications influenced the spatial variation of the seven DRASTIC parameters, bringing all of them to present adequate sensitivity to the DRASTIC work scale and the heterogeneities of the study area, approaching, undoubtedly, the real conditions found in the area of the Jacaré-Tietê System. Therefore, this work met the proposed objectives and brought significant contributions to the discussions concerning the changes in the DRASTIC method to assess the groundwater intrinsic vulnerability. Finally, it’s recommended that vulnerability estimation methods, selected according to their suitability to the different needs, be applied by the public authorities as tools for the zoning rules for soil land use and land cover aiming the water resources protection.